Formula Optimization of Sunscreen Lotion Leaves Muntingia calabura L. Extract - Nurista Dida Ayuningtyas; Agustina Putri Pitarisa S; Rizqi Adi Irfani (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2022)
Background : sunlight contains ultraviolet that happened skin problem from mild to severe. To overcome these problems, a sunscreen made from natural materials is relatively safe. CKersen Leaves (Muntingia calabura L.) contain total flavonoids and phenolics can be used as active ingredients. In lotion preparations, emulsifiers can affect the physical properties of lotions. Objective : from this research is to study the optimal emulgator composition of stearic acid and triethanolamine in 70% ethanol extract of Kersen Leaves. Method : stearic acid and triethanolamine will be optimized using Software Design Expert version 11 Simplex Lattice Design method. Formula was evaluated using organoleptic, homogeneity, pH, dispersibility, adhesion, and viscosity. Result : showed that 8 run of 70% ethanol extract of lotion leaves of Kersen (muntingia calabura L.) were homogeneous, had a brown color, typical odor of greentea with a pH of 6.64-8.06; spread capacity 5.32-6.18 cm; adhesion of 3.85-15.37 seconds and viscosity of 2000-3100 cp. Conclusion : optimal formula for lotion preparations obtained stearic acid 3.31% : triethanolamine 2.69%. T test results show the equation that applies to the pH response, adhesion and viscosity.